Novel Topical Liposomal Gel of Benzoyl Peroxide And Resveratrol For Treatment Of Acne - Kamra, Manju; Diwan, Anupama; Sardana, Satish (Asian Journal of Pharmaceutical Research and Development, 2018)
Liposomal formulations have been used in the treatment of a number of dermatological diseases . Benzoyl peroxide is the drug of choiceused for the treatment of acne but suffers from side effects such as skin redness, irritation, itching, oedema and dryness. In this research work benzoyl peroxide was encapsulated into liposomes, alongwith herbal drug resveratrol for treatment of acne . Liposomes were prepared by thin film hydration technique and evaluated for pH , particle size , zeta potential , FT -IR, XRD and TEM etc. which indicated suitable encapsulation of drugs in liposomes. Liposomal gel was prepared using different polymers and evaluated for colour, pH, drug content, homogeneity and grittiness and in vitro release studies .Suitable penetration enhancers were added to the selected preparation . The final selected formulation was evaluated further for viscosity, spreadibility ,drug release, kinetic study and stability studies .Selected liposomal gel showed prolonged release of both drugs and the product was found to be stable .Ex-vivo diffusion studies and drug deposition studies on animals was performed. Skin irritation studies on animals did not show any irritation,dryness or redness.